Rheumatologic associations of microscopic colitis: A narrative review. Issue 3 (22nd August 2022) - Le, Christopher; Zeffren, Noam; Kramer, Neil; Rosenstein, Elliot D
ABSTRACT: Extraintestinal manifestations (EIMs) are frequent complications of the classical inflammatory bowel diseases, Crohn's disease and ulcerative colitis. However, in addition to the classical diseases, there is a spectrum of conditions, often termed 'microscopic colitis' (MC), in which EIMs are less well described. Our objective was to review the literature regarding the EIMs complicating MC and describe their association with systemic autoimmune rheumatic diseases. A comprehensive search and review of peer-reviewed English-language and international journals and reports was completed based on key terms, including 'microscopic colitis', 'lymphocytic colitis', 'collagenous colitis', 'inflammatory bowel disease', and 'extraintestinal manifestations', and the specific disease associations utilizing the PubMed Central database and MEDLINE. A broad spectrum of rheumatologic manifestations has been reported in patients with MC. The identification of rheumatoid arthritis and limited scleroderma as comorbidities with MC was noteworthy. Inflammatory arthropathy was frequently seen in MC, usually preceding or occurring in conjunction with the onset of gastrointestinal symptoms. A variety of presentations of associated arthritis were reported: migratory, symmetric or asymmetric, peripheral or axial, oligoarticular or polyarticular, and erosive or non-erosive. There was a high incidence of autoantibodies in these patients, supporting a potential autoimmune association. On the basis of these anecdotal reports, we would suggest the development of a clinical registry to help define the incidence of EIMs and systemic autoimmune rheumatic diseases among MC patients to help elucidate shared predispositions, pathogenic mechanisms, and therapeutic opportunities.